Physical activity of high school students in the city of Cilegon, Banten Province - Sendy Mohamad Anugrah; Triprayogo, Rian; Zubaida, Ida (Universitas Nusantara PGRI Kediri, 2021)
Lifestyle in adolescence is very important to know to determine the development of a person's adult health level. The main objective of this study was to map the level of physical activity of high school students in Cilegon. This study used a survey study method of 3185 participants of high school level consisting of 985 males and 2200 females who participated in this study. Data on students' physical activity levels were obtained using a paper-based online IPAQ questionnaire. The results of this study indicated that the BMI categories for males were 37.5% underweight, 37.3% normal, 9.8% overweight, and 15.4% obese, while for females were 35.7% underweight, 46.4% normal, 9.3% overweight, and 8.6 obese. The findings in this study provided evidence that the BMI of high school students in Cilegon was in the normal or healthy weight category. However, in the BMI category, there were still many research subjects who were in the obese category. This was because the physical activities carried out by students were in a low category. The high percentage of the low activity category was feared that the subjects of this study would affect their health condition in the future